2017
DOI: 10.3390/nu9060623
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Vitamin D Supplementation on IGF-1 and Calcitriol: A Randomized-Controlled Trial

Abstract: Increasing evidence suggests a possible interaction between vitamin D and insulin-like growth factor-1 (IGF-1). We aimed to investigate effects of vitamin D supplementation on IGF-1 (primary outcome) and calcitriol (1,25(OH)2D) concentrations (secondary outcome). This is a post-hoc analysis of the Styrian Vitamin D Hypertension Trial—a single-center, double-blind, randomized, placebo-controlled trial (RCT) conducted from 2011 to 2014 at the Medical University of Graz, Austria. Two-hundred subjects with arteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
26
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 50 publications
4
26
0
1
Order By: Relevance
“…The fact that we were able to find a significant increase in FGF23 levels in subgroups with baseline 25(OH)D concentrations below 20 and 16 ng/mL but could not find a similar effect in the entire study cohort may be explained by a possibly higher increase in calcitriol in participants with lower baseline 25(OH)D concentrations [ 9 ], thus leading to a more pronounced rise in FGF23 concentrations due to increased intestinal phosphate absorption [ 22 ]. A significant increase in calcitriol concentrations after vitamin D3 supplementation within the population of the Styrian Vitamin D Hypertension trial has been reported previously [ 10 ].…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…The fact that we were able to find a significant increase in FGF23 levels in subgroups with baseline 25(OH)D concentrations below 20 and 16 ng/mL but could not find a similar effect in the entire study cohort may be explained by a possibly higher increase in calcitriol in participants with lower baseline 25(OH)D concentrations [ 9 ], thus leading to a more pronounced rise in FGF23 concentrations due to increased intestinal phosphate absorption [ 22 ]. A significant increase in calcitriol concentrations after vitamin D3 supplementation within the population of the Styrian Vitamin D Hypertension trial has been reported previously [ 10 ].…”
Section: Discussionsupporting
confidence: 52%
“…Since vitamin D supplementation leads to a suppression of PTH and an increase in calcitriol concentrations [ 9 , 10 ], a resulting rise in serum phosphate levels may in turn stimulate the synthesis of FGF23. Considering its potential adverse effects on various health outcomes, several previous studies aimed to investigate a possible effect of vitamin D supplementation on FGF23 concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…A similar positive correlation between 25(OH)D concentrations and serum IGF-1 concentrations was found in healthy subjects (Gómez et al, 2004;Bogazzi et al, 2011). It is known that an adequate vitamin D level supports normal bone turnover but the results of the studies evaluating correlations between vitamin D and BTMs are divergent (Barnes et al, 2006;Lee et al, 2013;Larijani et al, 2016;Ciresi et al, 2017;Schwetz et al, 2017;Trummer et al, 2017;Witkowska-Sędek et al, 2017). Previously published studies by Schwetz et al (2017), Wamberg et al (2013) and Seamans et al (2010), which enrolled, respectively, adults with arterial hypertension, obese subjects and healthy adults did not find any significant associations between vitamin D supplementation and BTMs.…”
Section: Discussionmentioning
confidence: 96%
“…Epidemiological studies have suggested that serum IGF-1 level correlates with fracture risk, bone density and bone mass (Rosen, 2004;Niu et al, 2005;He et al, 2006;Léger et al, 2007;Locatelli et al, 2014;Devesa et al, 2016). Several authors have evaluated the association between the GH/IGF-1 axis and vitamin D status (Gómez et al, 2004;Bogazzi et al, 2011;Ameri et al, 2013;Witkowska-Sędek et al, 2016;Ciresi et al, 2017;Trummer et al, 2017). The study by Ameri et al (2013) showed that vitamin D could increase circulating IGF-1 level in adults and better vitamin D status may facilitate the achievement of normal IGF-1 values in GHD.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, we cannot exclude osteomalacia in both groups of patients, as we did not perform histological evaluation. We did not treat vitamin D deficiency before the enrollment because there are conflicting data on the effects of vitamin D supplementation on IGF1 in adults (54,55) and it is known that IGF1 increases the circulating levels of 1,25-dihydroxyvitamin D by stimulating the expression and activity of 1α-hydroxylase (54).…”
Section: Discussionmentioning
confidence: 99%